(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
With the rapid development of digital technologies, social media platforms such as Facebook, Instagram, Telegram, and TikTok have become an integral part of daily life. According to the World Health Organization, internet usage among young people exceeds 90%, with a substantial proportion dedicated specifically to social media.